Environmental Nexus: And You’ll Recognize Us by Our Places - Lineu Castello; Marcos Petroli (Challenging Issues on Environment and Earth Science Vol. 5, 2021)
The sites of an urban zone inside a Biosphere Reserve in southern Brazil are investigated in this research, as well as the potential for synergy between their biological and social systems. It assumes: (i) that the perception of their regional rootedness works beneficially for enhancing sustainability; (ii) that the current progress in the conceptualization of “place” contributes to the quest of sustainability, since the core factors of the concept deal precisely with the relationship between people and environment. This article examines how people see real and imagined environments, as well as the many forms of perception that they elicit. . Real places are considered as socially built, while invented places are seen as economically promoted. The following criteria were used to choose empirical regional cases: Perception (actual and imagined locations), size (urban and ex-urban), and management (public or private). Place is a built environmental form filled with symbolic meaning to its users in the field of Architecture-Urbanism. With the current paradigm shift from modernism to postmodernism, the discipline is evolving toward a more thorough concern with the philosophical implications of places on phenomenological grounds. Furthermore, the construction and marketing of new places are becoming widely acknowledged as powerful tools for fostering wealth and well-being, thanks to the economic progress linked to place creation. The combined private and public management of the region’s places and the restrained design they presently employ are providing grounds for an affluent development, showing a wise use of the regional resources. Overall, it appears that residents have learnt to operate in harmony with the environment. This hints at a clear manifestation of sustainable development, worth investigating. Presumably, because it sits at the crossroads of physical, social, economic, and behavioural sciences, the idea of place appears to be a promising approach of addressing the issues of long-term regional development planning.